2013
DOI: 10.1111/cei.12158
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of splenic CD8+ T cell exhaustion in patients with hepatitis C

Abstract: Summary There is increasing interest in the role of T cell exhaustion and it is well known that the natural history of chronic hepatitis C virus infection (HCV) is modulated by CD8+ T cell immunobiology. There are many pathways that alter the presence of exhaustive T cells and, in particular, they are functionally impaired by inhibitory receptors, such as programmed death-1 (PD-1) and T cell immunoglobulin and mucin domain-containing protein 3 (Tim-3). We obtained spleen, liver and peripheral blood (before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Moreover, TCR-induced responses by Tim-3 + CD8 T cells were augmented by the addition of a soluble form of Tim-3 or Tim-3-specific antibodies, suggesting that Tim-3 enforces functional impairment. Following this report, several studies showed that the frequencies of Tim-3 + CD8 T cells were elevated in PBL from patients chronically infected with HBV or HCV and that these cells were in a dysfunctional state, with some of these studies providing evidence that impairment of CD8 T cell function was at least partly dependent on Tim-3 [76, 87, 86, 89, 99, 92]. …”
Section: Regulation Of Cd8 T Cell Responses By Tim-3mentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, TCR-induced responses by Tim-3 + CD8 T cells were augmented by the addition of a soluble form of Tim-3 or Tim-3-specific antibodies, suggesting that Tim-3 enforces functional impairment. Following this report, several studies showed that the frequencies of Tim-3 + CD8 T cells were elevated in PBL from patients chronically infected with HBV or HCV and that these cells were in a dysfunctional state, with some of these studies providing evidence that impairment of CD8 T cell function was at least partly dependent on Tim-3 [76, 87, 86, 89, 99, 92]. …”
Section: Regulation Of Cd8 T Cell Responses By Tim-3mentioning
confidence: 96%
“…Studies employing mice have demonstrated that Tim-3 is essentially absent on naïve CD8 T cells but is expressed by CD8 T cells that become activated due to microbial infection [80, 37, 81-85]. In addition, a number of studies involving mice or human samples have shown that chronic infections result in high levels of Tim-3 expression by activated CD8 T cells [74, 76, 86, 87, 81, 88, 79, 89-92]. Lastly, data from mouse cancer models or analysis of patient samples revealed that CD8 T cells infiltrating tumors express Tim-3 [93-98].…”
Section: Regulation Of Cd8 T Cell Responses By Tim-3mentioning
confidence: 99%
“…Tim-3 expression is largely absent on naïve CD8 T cells but is induced on CD8 T cells activated by acute microbial infections [56,170,174,[181][182][183][184]. It has also been shown that chronic infections in humans or mice lead to expression of Tim-3 on activated CD8 T cells [56,[185][186][187][188][189][190][191][192][193][194]. Lastly, Tim-3 expression has been demonstrated on tumor infiltrating lymphocyte (TIL) CD8 T cells from mouse cancer models as well as cancer patient samples [195][196][197][198][199][200].…”
Section: Regulation Of Cd8 T Cell Responses By Tim-3mentioning
confidence: 99%
“…Additionally, CD8 T cell responses were augmented by addition of soluble Tim-3 or Tim-3 antibody. Several reports that followed demonstrated that Tim-3 + CD8 T cells were elevated in HBV or HCV-infected patients and that these cells were also dysfunctional [185,188,189,191,193,201].…”
Section: Regulation Of Cd8 T Cell Responses By Tim-3mentioning
confidence: 99%
See 1 more Smart Citation